THE ROLE OF INNOVATION IN THE DEVELOPMENT OF COMMERCIAL AND INDUSTRIAL ENTERPRISES - Belkin, Yurii; v, Alla; Sedova, Nadezda; Sorokina, Anna (Revista Inclusiones, 2020)
The modern transition economy is characterized by accelerated changes in both productive forces and industrial relations. At the same time, it is important to discover patterns behind individual changes, knowledge of which increases the level of organization of the organization's commercial activities. On the one hand, there is an acceleration of information, commodity and financial flows, the widespread use of the latest equipment and technologies in the practice of companies, the modification of its functions, there is a complication and expansion of the variability of the organization of its relations, new mechanisms for the use of economic laws appear.